PENGARUH MOTIVASI BERBELANJA HEDON, PROMOSI PENJUALAN DAN GAYA HIDUP BERBELANJA TERHADAP PEMBELIAN IMPULSIF PENGGUNA E-COMMERCE SHOPEE - Berlien, Richard; Calen, Calen; Sinaga, Novendra Adisaputra (Politeknik Bisnis Indonesia, 2024)
This research aims to determine the influence of hedonic shopping motivation, sales promotions and shopping lifestyle on the impulse buying of Shopee e-commerce users, both simultaneously and partially. The type of research used in this research is quantitative research. The population in this study was 45 employees at PT.Metro Makmur Jaya Pematang Siantar. Simultaneously, hedonic shopping motivation, sales promotions and shopping lifestyle influence the impulse buying of Shopee e-commerce users. Impulse buying which is influenced by hedonic shopping motivation, sales promotions and shopping lifestyle is 70% while the remaining 30% is influenced by other factors not examined in this research.